SAVING INTENTION THROUGH KNOWLEDGE AND RELIGIOSITY AT ISLAMIC BANKS - Luthfiany, Delia; Silaningsih, Endang; Kartini, Tini (Universitas Nusa Cendana, 2025)
The research aims to analyze the level of saving intention at Bank Syariah Indonesia (BSI) KCP Bogor Jalan Baru by examining the influence of knowledge and religiosity. The research utilizes a sample of 100 respondents and adopts a quantitative methodology, employing multiple linear regression analysis with the aid of IBM SPSS 25. The findings reveal that the combined effect of these two variables is also found to be significant in influencing saving intention; both knowledge and religiosity individually exert a positive and significant impact on saving intention at the selected branch. It is suggested that future research consider employing alternative methodologies, such as qualitative approaches, to gain deeper insight into the observed phenomena. Keywords: Knowledge; Religiosity; Saving intention